ANALISIS PENGARUH DER, DPR, ROE DAN SIZE TERHADAP PBV PERUSAHAAN MANUFAKTUR YANG LISTING DI BEI PERIODE 2005-2007 - Hidayati, Eva Eko (Magister Manajemen, Fakultas Ekonomika dan Bisnis Undip, 2010)
PBV is the relationship between stock market price and book value per share. This ratio measures the value given by financial market to the management and organization as a firm continuous to grow. PBV shows ability of firm creating a relative value of the firm toward the capital invested. The higher the ratio PBV, The more successful the firm creating a value for shareholders. This study is aimed to examine the influence of debt to equity ratio, dividend payout ratio, return on equity and size toward price book value. Population of this study is all manufacturing firm listed on IDX during 2005-2007. By using purposive sampling, the written got 24 firms to be the sample. This study used multiple regression analysis technique using SPSS, in previously, the data were examined using classical assumption test such as test of normality, multicolinierity, and autocorrelation. The result shows that debt to equity ratio, dividend payout ratio, return on equity and size, all of them have a role towards price book value with 75,9% of adjusted R2 . Individually debt to equity ratio and dividend payout ratio have a negative relation and insignificant toward price book value while return on equity and size have positive relation and significant toward price book value.Â